Phospholipase D inhibitor enhances radiosensitivity of breast cancer cells - Cheol Son, Ju (Nature Publishing Group, 2013)
Radiation and drug resistance remain the major challenges and causes of mortality in the treatment of locally advanced, recurrent and metastatic breast cancer. Dysregulation of phospholipase D (PLD) has been found in several human cancers and is associated with resistance to anticancer drugs. In the present study, we evaluated the effects of PLD inhibition on cell survival, cell death and DNA damage after exposure to ionizing radiation (IR). Combined IR treatment and PLD inhibition led to an increase in the radiation-induced apoptosis of MDA-MB-231 metastatic breast cancer cells. The selective inhibition of PLD1 and PLD2 led to a significant decrease in the IR-induced colony formation of breast cancer cells. Moreover, PLD inhibition suppressed the radiation-induced activation of extracellular signal-regulated kinase and enhanced the radiation-stimulated phosphorylation of the mitogen-activated protein kinases p38 and c-Jun N-terminal kinase. Furthermore, PLD inhibition, in combination with radiation, was very effective at inducing DNA damage, when compared with radiation alone. Taken together, these results suggest that PLD may be a useful target molecule for the enhancement of the radiotherapy effect.